Single-cell protein expression of hiPSC-derived cardiomyocytes using Single-Cell Westerns. (December 2020) - Jabart, Eric; Molho, Josh; Sin, Kristina; Stansfield, Ben; Kazmouz, Sobhi G.; Ventro, Daniela; Gardner, Kelly; Wu, Joseph C.; Churko, Jared M.
Abstract: The ability to reprogram human somatic cells into human induced pluripotent stem cells (hiPSCs) has enabled researchers to generate cell types in vitro that have the potential to faithfully recapitulate patient-specific disease processes and phenotypes. hiPSC-derived cardiomyocytes (hiPSC-CMs) offer the promise of in vitro patient- and disease-specific models for drug testing and the discovery of novel therapeutic approaches for treating cardiovascular diseases. While methods to differentiate hiPSCs into cardiomyocytes have been demonstrated, the heterogeneity and immaturity of these differentiated populations have restricted their potential in reproducing human disease and the associated target cell phenotypes. These barriers may be overcome through comprehensive single-cell characterization to dissect the rich heterogeneity of hiPSC-CMs and to study the source of varying cell fates. In this study, we optimized and validated a new Single-Cell Western method to assess protein expression in hiPSC-CMs. To better understand distinct subpopulations generated from cardiomyocyte differentiations and to track populations at single-cell resolution over time, we measured and quantified the expression of cardiomyocyte subtype-specific proteins (MLC2V and MLC2A) using Single-Cell Westerns. By understanding their heterogeneity through single-cell protein expression and quantification, we may improve upon current cardiomyocyte differentiation protocols, generate hiPSC-CMs that are more representative of in vivo derived cardiomyocytes for disease modeling, and utilize hiPSC-CMs for regenerative medicine purposes. Single-Cell Westerns provide a robust platform for protein expression analysis at single-cell resolution. Graphical abstract: Unlabelled Image Highlights: Single-Cell Westerns allow protein quantification of cardiomyocytes at single-cell resolution. Single-Cell Westerns can detect and resolve off-target antibody binding. A subpopulation of hiPSC-CMs expresses MLC2A followed by co-expression of MLC2A and MLC2V.